2019
DOI: 10.1093/bioinformatics/btz138
|View full text |Cite
|
Sign up to set email alerts
|

deTS: tissue-specific enrichment analysis to decode tissue specificity

Abstract: Motivation Diseases and traits are under dynamic tissue-specific regulation. However, heterogeneous tissues are often collected in biomedical studies, which reduce the power in the identification of disease-associated variants and gene expression profiles. Results We present deTS, an R package, to conduct tissue-specific enrichment analysis with two built-in reference panels. Statistical methods are developed and implemented … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 52 publications
(73 citation statements)
references
References 24 publications
2
68
0
Order By: Relevance
“…These 13 traits included lots of psychiatric disorders, including attention deficit hyperactivity disorder, autism spectrum disorder, bipolar disorder, major depressive disorder and schizophrenia. To extend our previous tissue-level study (Pei et al 2019), we found that for most neuropsychiatric diseases, their susceptible genes were mainly enriched in excitatory and inhibitory neurons (Fig. 8).…”
Section: Cell-type Specific Enrichment Analysis Of 13 Major Brain Asssupporting
confidence: 60%
“…These 13 traits included lots of psychiatric disorders, including attention deficit hyperactivity disorder, autism spectrum disorder, bipolar disorder, major depressive disorder and schizophrenia. To extend our previous tissue-level study (Pei et al 2019), we found that for most neuropsychiatric diseases, their susceptible genes were mainly enriched in excitatory and inhibitory neurons (Fig. 8).…”
Section: Cell-type Specific Enrichment Analysis Of 13 Major Brain Asssupporting
confidence: 60%
“…We will evaluate these association signals using additional annotations such as epigenetic marks, expression quantitative trait loci (eQTL), tissue-specificity and cell types, among others. Tissue specificity enrichment analysis of genetic variations in association studies has shown interesting results, as demonstrated in our multitrait GWAS analysis [60]. Finally, further experimental validation of supported and proposed MS mechanisms is needed using cell lines and animal models.…”
Section: Limitations and Future Workmentioning
confidence: 67%
“…To identify the disease-related tissues of AUD, we first applied tissue-specific enrichment analysis (TSEA) of the AUD GWAS data and determined three tissues for AUD: pituitary (the most significant raw p=3.2 × 10 -4 ), brain cerebellum (raw p=8.9 × 10 -4 ), and liver (p=1.5 × 10 -3 ) (see below). We further applied a widely used online tool, FUMA, to validate the TSEA by deTS 29 30. As a result, FUMA identified four frequently occurred AUD-associated tissues: brain cerebellum (raw p=0.02), brain frontal cortex (BA9) (raw p=0.02), brain hippocampus (raw p=0.02), and pituitary (raw p=0.03).…”
Section: Resultsmentioning
confidence: 99%
“…To identify the tissues that are most likely related with AUD, we applied two methods to determine the AUD-associated tissues, the decoding Tissue Specificity (deTS) package developed in our previous work29 and the Functional Mapping and Annotation (FUMA) 30. DeTS is an R package that provides a panel with 47 tissues from the GTEx V.7 expression data and implements Fisher’s exact test to examine whether genes in a query list are enriched in a tissue.…”
Section: Methodsmentioning
confidence: 99%